Recombinant human thyrotropin stimulated 131I treatment for multinodular goiter - Tang, Limin; Ma, Tiekun; Wu, Fengyu (Nuklearmedizin - NuclearMedicine, 2016)
The aim of the study was to investigate the effects of rhTSH stimulation before 131I treatment in patients with MNG. Methods: Sources included the Cochrane Library, MEDLINE, EMBASE, and SCOPUS database (all until January 2016). Randomized controlled trials (RCTs) that assessed the efficacy of rhTSH-stimulated 131I treatment compared to placebo or 131I treatment alone were collected. Two authors performed the data extraction independently. Results: Six RCTs involving 294 patients with MNG were included in this review. Altogether 168 patients were randomized to rhTSH-stimulated 131I therapy, and 126 to either placebo and 131I or 131I alone. rhTSH-stimulated 131I vs placebo and 131I or 131I alone for MNG showed no statistically significant difference in quality of life and all-cause mortality. rhTSH- (at a dose of 0.03 mg and above) stimulated 131I treatment for MNG showed significant benefits in thyroid volume reduction. 131I treatment with rhTSH stimulation at high doses (0.03 mg, 0.1 mg, 0.3 mg and 0.45 mg) for MNG caused significantly higher adverse effects and hypothyroidism. Conclusions: The overall results indicated that using rhTSH at high doses of 0.03–0.45 mg before 131I therapy resulted in a greater TVR than 131I therapy alone for patients with non-toxic MNG. However, an increased incidence of adverse effects and hypothyroidism was observed in patients receiving highdose of rhTSH pretreatment than in patients who received low-dose rhTSH pretreatment. Therefore, a dose of 0.03 mg rhTSH pretreatment before 131I therapy may be more potent than 131I alone in treating patients with non-toxic MNG who either had a contraindication for or declined surgery.
Keywords: Goiter; rhTSH